Pemberdayaan Anak Jalanan melalui Sanggar Karya Anak Bangsa - Siti Aminatun (Balai Besar Litbang Pelayanan Kesejahteraan Sosial, 2013)
This study meant to describe the activities done by Sanggar Karya Anak Bangsa (Kabasa) which commited to children vulnerable being in the street, street children, and ex-street children, to be motivated leaving the street. Data were gathered through observation, in-depth interview, and documentary analysis. The study showed that Sanggar Kabasa was set to educate children vulnerable being in the street, street children, and ex-street children, so the they can escape street lives. Sanggar Kabasa as government partner has been participating actively to educate street children. Its funding limit was solved by joint venture with any institution commiting to street children, suc as Kemandirian Dompet Dhuafa, through vocational trainning to get a better job. Joint venture also done with individual commiting to street children through fund and means of education. Sanggar Kabasa maked administrative report routinely to donateurs on the use of the fund and aid to show that their commitment was very worthwhile for street children. Based on the study is recommended that any non-government institution commited to sosial affairs (street children) should be taken by the government as partner, so the their existence should be supported by the government. The sinergy among government, non-government institution, and communities commited to sosial problems (street children) when is done hand-in-hand and sosial solidarity hopefully can solve existing sosial problem.